Sagittal Root Position of Maxillary Anterior Teeth in Nepalese Population Using Cone Beam Computed Tomography - Lamichhane, S.; Humagain, M.; Dawadi, A.; Koju, S. (Kathmandu University Medical Journal, 2022)
Background There are no radiographic studies in Nepalese population for determination of sagittal root positioning in maxillary anterior teeth. The sagittal root positioning and root angulation plays a vital role for case selection in immediate implant placement.Objective To evaluate, classify and compare sagittal root position between different maxillary anterior teeth.Method A 2-year retrospective study was conducted on 100 patients (53 males and 47 females) who fulfilled the inclusion criteria using cone beam computed tomographic images. The relationship of root of tooth to its alveolar housing were recorded as Class I to IV. In addition, the root angulation relative to the alveolar process was also measured.Result The sagittal root position (SRP) calculated on six maxillary anterior teeth on average was found to be 87.83% for Class I, 6.67% for Class II, 0.67% for Class III and 5.17% for Class IV respectively. The mean root angulation was found to be higher with canines on both side whereas lateral incisors had lesser mean root angulation. Root angulation of maximum teeth were between 10-20 degrees where immediate implant placement is possible.Conclusion Within the limitations of this study, the sagittal root positioning and root angulation in Nepalese population showed a favorable result for immediate implant placement. Maximum teeth were found to be close to the alveolar process with the exception of few teeth.